1979
DOI: 10.1042/bj1840367
|View full text |Cite
|
Sign up to set email alerts
|

A releationship between protein-degradation rates in vivo, isoelectric points, and molecular weights obtained by using density labelling

Abstract: 1. Half-lives of five plant enzymes were estimated by rate-labeling with 2H2O on the assumption that loss of catalytic activity is equivalent to protein degradation. 2. This involved measuring band-broadening of activity profiles after isopycnic centrifugation. 3. Isoelectric points were determined by isoelectric focusing, and molecular weights were estimated by gel filtration. 4. The conclusion is drawn from the experimental evidence presented that a weak correlation exists between rates of degradation and is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1982
1982
1988
1988

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…The degradation of both subunits of RuBPCase followed different kinetics, the larger subunit being more rapidly degraded than the small subunit, which needed incubation times longer than 4 h to undergo detectable degradation (data not shown). This could be explained by the different mol wt of both subunits, in accord with the general scheme proposed for other proteolytic systems (1,10 have failed to detect such intermediates. As pointed out by Muller et al (23), the failure to demonstrate intermediates in the degradation processes may be explained by the fact that they might be short-lived or unrecognizable by antibodies.…”
Section: Resultsmentioning
confidence: 52%
“…The degradation of both subunits of RuBPCase followed different kinetics, the larger subunit being more rapidly degraded than the small subunit, which needed incubation times longer than 4 h to undergo detectable degradation (data not shown). This could be explained by the different mol wt of both subunits, in accord with the general scheme proposed for other proteolytic systems (1,10 have failed to detect such intermediates. As pointed out by Muller et al (23), the failure to demonstrate intermediates in the degradation processes may be explained by the fact that they might be short-lived or unrecognizable by antibodies.…”
Section: Resultsmentioning
confidence: 52%
“…Because of the difference in molecular weight of the two subunits, it oiight be expected that their degradation (i.e. the disappearance of the SDS-PAGE bands) should not occur at the same rate, the larger subunit being more rapidly hydrolyzed than the smaller (Dice andGoldberg 1975, Acton andGupta 1979). Our experiments showed just the opposite, at least at pH 3.7 and 4.5, indicating a preference of the proteolytic enzymes for the small subunits.…”
Section: Diseussionmentioning
confidence: 58%
“…Evidence supporting the existence of a correlation between the physical properties of proteins (charge and size) and their rates of degradation has been reviewed by Goldberg and St. John (17). A number of experiments, designed to test these correlations in plants, produced results broadly consistent with the general hypothesis (1,10). However, more recent experiments, employing different methods, have suggested that, if the correlations exist, they are at best weak (8,9).…”
mentioning
confidence: 83%
“…Two batches of Lemna fronds were grown in complete medium (750 ml) containing either 1 The results of this experiment are shown in Figure 7. The pattern of protein degradation in darkness is significantly different from that observed in the light.…”
Section: Uferreira and Daviesmentioning
confidence: 99%